A Survey of Nanoindentation Studies on HPT‐Processed Materials. Issue 1 (21st January 2020) - Choi, In-Chul; Jang, Jae-il
Abstract : For better understanding of the relation between refined microstructure and mechanical behavior of high‐pressure torsion (HPT) processed materials, the nanoindentation technique has been widely used under various rate and temperature conditions, as described by Jae‐il Jang and In‐Chul Choi in article number 1900648 . The technique makes it possible to estimate various mechanical properties of the local regions within a HPT disc.